Health-Promoting Effects of Traditional Foods - Iriti, Marcello; Iriti, Marcello (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food cannot be only considered a combination of constituents with different nutritional values, but its relevance for humans can be fully understood by also taking into account other aspects such as history, culture, ecology, and the environment. Overall, assuming that access to food is secured for all people, traditional dietary patterns are considered safe in terms of longevity, healthy ageing, and morbidity. Indeed, healthy diets have been associated with a reduced risk and incidence of chronic degenerative diseases including cardiovascular disease, type 2 diabetes, metabolic syndrome, certain types of cancers, and neurodegenerative disorders. In general, healthy dietary habits include a low consumption of refined sugars, red meat, and saturated fats, as well as a high intake of fruit, vegetables, legumes, low-fat dairy products, and healthy lipids (from seafood). As an example, the Mediterranean diet can be considered the archetype of a health-promoting lifestyle by virtue of the phytochemical diversity of its food components.
English
Keywords: Research & information: general; Biology, life sciences; Food & society; Verbenaceae; isoprenoids; -caryophyllene; flavonoids; anthocyanins; antiradical capacity; DPPH; maqui; murta; calafate; arrayán; Chilean strawberry; berries; functional foods; Mangifera indica; mango; UPLC; ESI-MS; polyphenols; xanthonoids; gallotannins; hydroxybenzophenones; mass spectrometry; antioxidant; antitumoral; corn silk; cumin; tamarind; aqueous extracts; form; postprandial glycemia; postprandial insulinemia; advanced glycation end products; anti-glycation; glycative stress; glyoxalase; methylglyoxal; cytokine; nutrients; food composition; African; Caribbean; macronutrients; energy; vitamins and minerals; wild Italian Prunus spinosa L. fruit; blackthorn; phenolic compounds; antimicrobial; ceramides; lipids; functional food; nutraceuticals; traditional food; Mediterranean diet; Nordic diet; overweight